Improving Access to Self-Expanding Metal Stents for Patients With Esophageal Cancer in Eastern Africa: A Stepwise Implementation Strategy. (2021) - Mushi, Beatrice P.; Mwachiro, Michael M.; Buckle, Geoffrey; Kaimila, Bongani N.; Mulima, Gift; Kayamba, Violet; Kelly, Paul; Akoko, Larry; Mmbaga, Elia J.; Selekwa, Msiba; Ringo, Yona; Pritchett, Natalie; et al.
Abstract : PURPOSE: The eastern corridor of Africa is affected by a high burden of esophageal cancer (EC), with > 90% of patients presenting with advanced disease. Self-expanding metal stents (SEMS) have been previously reported as safe and effective for palliation of malignant dysphagia in resource-limited settings; however, access is limited throughout Eastern Africa. METHODS: In response to demand for palliative interventions for patients with dysphagia because of EC, the African Esophageal Cancer Consortium (AfrECC) partnered with the Clinton Health Access Initiative to improve access to SEMS in Eastern Africa. We undertook a stepwise implementation approach to (1) identify barriers to SEMS access, (2) conduct a market analysis, (3) select an industry partner, (4) establish regulatory and procurement processes, (5) develop endoscopic training resources, (6) create a medical device registry, and (7) establish principles of accountability. RESULTS: Following an evaluation of market demand and potential SEMS manufacturers, Boston Scientific Corporation announced its commitment to launch an access program to provide esophageal SEMS to patients in Tanzania, Kenya, Malawi, and Zambia at a subsidized price. Parallel regulatory and procurement processes were established in each participating country. Endoscopy training courses were designed and conducted, using the Training-of-Trainers model. A device registry was created to centralize data for quality control and to monitor channels of SEMS distribution. Principles of accountability were developed to guide the sustainability of this endeavor. CONCLUSION: The AfrECC Stent Access Initiative is an example of a multisector partnership formed to provide an innovative solution to align regional needs with a supply chain for a high-priority medical device.